LISA Pathfinder mission extension: A feasibility analysis. Issue 12 (15th June 2019) - Dei Tos, Diogene A.; Rasotto, Mirco; Renk, Florian; Topputo, Francesco
Abstract: A proposed mission extension for LISA Pathfinder involved redirecting the probe to the Sun–Earth gravitational saddle point. Realistic models for both space and ground segments were used to carry out a number of analyses for trajectory design, orbit determination, and navigation cost. In this work, we present the methods that allow assessing the feasibility of flying general limited-control-authority spacecraft in highly nonlinear dynamics, and in particular of the proposed mission extension in a statistically reliable approach. Solutions for transfers from the Sun–Earth L 1 and L 2 to the saddle point are shown, which feature very low Δ v consumption, from few centimeters per second to 10 m/s. The analysis is then specialized to the case of LISA Pathfinder, for which several solutions are presented. This work gives evidence that LISA Pathfinder might have been able to fly-through the saddle point, provided initial tracking errors within 10 km in each position component and 0.1 m/s in each velocity component. A critical discussion on the opportunistic mission extension is eventually made.